PENGGUNAAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS VI SD NEGERI 008 PULAU RUMPUT - Safarilis Safarilis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The background of this study is the low learning outcomes of students' Civics, which can be seen in the studentscores. Of the 21 students the number of students who reached KKM as many as 9 people with an average class65.45. KKM that has been established school that is 73. For that done improvement of learning process byapplying direct learning model. This research is a classroom action research, conducted at SD Negeri 008Pulau Rumput. The subject of this research is the students of class VI with the number of 21 students. Based onthe research results obtained data that student learning outcomes have increased on the basic score of 65.45average score increased in the first cycle to 76.62. At UH II it increased to 81.08. The individual completeness ofthe basic score that originally 9 people increased in the first cycle as many as 16 people and on the second cycleincreased again to 21 people.